2020
DOI: 10.1186/s13756-020-00841-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroquinolone resistance of Staphylococcus epidermidis isolated from healthy conjunctiva and analysis of their mutations in quinolone-resistance determining region

Abstract: Background Staphylococcus epidermidis is the most common pathogen in postoperative endophthalmitis and causes various infectious eye diseases. However, there is very little information on fluoroquinolone antibiotic resistance to S. epidermidis identified in conjunctival microbe and analysis of related genes. Here, the authors investigated the rate of resistance to fluoroquinolones of Staphylococcus epidermidis isolated from normal conjunctival microbes and mutations in the quinolone-resistance determining regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…cn/ VFs/) was used for virulence gene annotation, with coverage≥95% and identity≥95% (Gupta et al 2019). Additionally, quinolone resistance determining regions (QRDR) were analyzed by SnapGene Viewer V. 1.5.2 software (Kang et al 2020). Graphpad prism V. 8.0.2 was used for heat map mapping of antimicrobial resistance genes and virulence genes.…”
Section: Whole Genome Sequencing (Wgs)mentioning
confidence: 99%
“…cn/ VFs/) was used for virulence gene annotation, with coverage≥95% and identity≥95% (Gupta et al 2019). Additionally, quinolone resistance determining regions (QRDR) were analyzed by SnapGene Viewer V. 1.5.2 software (Kang et al 2020). Graphpad prism V. 8.0.2 was used for heat map mapping of antimicrobial resistance genes and virulence genes.…”
Section: Whole Genome Sequencing (Wgs)mentioning
confidence: 99%
“…Isolates were digested with the restriction enzyme XbaI (3µL, 15U/µL). The gels were run at 6.0 V/cm with an initial/final switch time of 2 s/60 sec at an angle of 120° at 0° for 20 h. The Salmonella serovar Braenderup H9812 standard served as size markers [ 41 ]. Specific experimental methods were performed as previously described [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The current dataset is limited to 20,000 Da, meaning that instead of detecting the true protein involved in resistance, the models likely detect a different protein or peptide encoded within the same plasmid involved in the same antibiotic resistance mechanism (Lau et al, 2014). For example, previous studies have demonstrated that the primary mutation responsible for ciprofloxacin resistance are mutations in the gyrA and parC genes, which have masses of 100,144 Da and 91,145 Da, respectively (Kang et al, 2020). Such proteins are outside of the detection range and are therefore not considered when building the model, demonstrating that although model performance may not be optimized to detect the main resistance biomarker directly, highly accurate results can still be achieved by detecting other smaller but related proteins.…”
Section: Discussionmentioning
confidence: 99%